Rare earth nanoparticles binding toluidine blue o for photodynamic treatment. - Hua, Yudan. (2012)
Rare earth nanoparticles exhibit various physical and chemical properties which are very worthy to explore. In this experiment, NaYF4: Yb, Er (20%,3%), the most efficient upconversion nanoparticles, used to bind with photosensitizer: toluidine blue O after surface modification. The FTIR, UV-visible and emission detection indicated that the nanoparticles conjugated to the toluidine blue O successfully and the energy transferred from nanoparticles to photosensitizer.